Workshop to strengthen the capacity of scientists from CGIAR Centres and NARS to deal with genetic resources policy issues, 27-30 November 2017, ICARDA, Rabat, Morocco. - CGIAR Genebank Platform (Bioversity International, 2018)
The CGIAR Genebank Platform Policy Module, in coordination with the International Center for Agricultural Research in Dry Areas (ICARDA), organized the ‘Workshop to strengthen the capacity of scientists from CGIAR Centres and National Agricultural Research Systems (NARS) to deal with genetic resources policy issues’. The workshop was held on 27-30 November 2017, at the ICARDA campus, in Rabat, Morocco. 41 participants from 7 CGIAR Centres and 9 national partner organizations participate in the workshop. The workshop was designed to increase participants’ understanding of how international laws promoting the conservation and sustainable use of genetic resources and benefit-sharing can apply to the day-to-day management of genebanks, plant breeding programmes and other forms of agricultural research and development. The workshop included experts’ presentations (including from the Secretariat of the International Treaty on Plant Genetic Resources for Food and Agriculture and the Secretariat of the Convention on Biological Diversity) and participatory analyses of practical case studies and hypothetical scenarios where the interface between the Nagoya Protocol and the ITPGRFA can raise legal and procedural issues.